2012
DOI: 10.28945/1584
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors for Implementing Business Intelligence Systems in Small and Medium Enterprises on the Example of Upper Silesia, Poland

Abstract: The main objective of this article is to identify the critical success factors (CSFs) for Business Intelligence (BI) systems implementation in small and medium enterprises (SMEs).The structure of the article is subordinated to this objective. The paper identifies the term Business Intelligence, characteristics of Business Intelligence systems, and various perspectives of their development. Then, the existing CSFs of IT projects and BI projects proposed by various authors in literature are reviewed. Next, on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 39 publications
4
134
0
4
Order By: Relevance
“…Therefore, organizations tend to havea higher adoption level, if they appoint a project champion who has a related background to the innovation under consideration (Chong et al, 2009;Puklavec & Oliveira, 2014). Many studies have consistently found that the presence of a champion enabled the adoption, is a determinant and played a significant role (Gu et al, 2012;Hwang et al, 2004; C.-P. Lee & Shim, 2007;C. Olszak & Ziemba, 2012;Puklavec & Oliveira, 2014;Yeoh & Koronios, 2010).…”
Section: Organizational Factors 1 Organizational Sizementioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, organizations tend to havea higher adoption level, if they appoint a project champion who has a related background to the innovation under consideration (Chong et al, 2009;Puklavec & Oliveira, 2014). Many studies have consistently found that the presence of a champion enabled the adoption, is a determinant and played a significant role (Gu et al, 2012;Hwang et al, 2004; C.-P. Lee & Shim, 2007;C. Olszak & Ziemba, 2012;Puklavec & Oliveira, 2014;Yeoh & Koronios, 2010).…”
Section: Organizational Factors 1 Organizational Sizementioning
confidence: 99%
“…In addition, extant literature shows that there are few empirical studies when it comes to organizational adoption of BI Systems based on adoption theories (DOI, TOE, INT) as many have been done at the individual level (Grublješič & Jaklič, 2015;Hou, 2014;Hou, 2012;Kester & Preko, 2015;Pilz & Ferraz, 2013;Yoon, Ghosh, & Bong-Keun Jeong, 2014). Also, most of the existing studies have focused mainly on Maturity Models (MMs) for measuring the current state of BI Systems as well as Critical Success Factors (CSFs) for BI Systems implementation in large organizations and Small Medium Enterprises (SMEs) in different parts of the world especially advanced economies (Dawson & Van Belle, 2013;Fedouaki & El Alami, 2013;Hawking, Jovanovic, & Sellitto, 2011;Hawking, 2013;Khojasteh, 2013;Mungree et al, 2013;Olbrich et al, 2012;Olszak & Ziemba, 2012;Olszak, 2013;Ong & Siew, 2013;Hribar Rajterič, 2010;Yeoh et al, 2008; ISSN: 2414-309X DOI: 10.20474/jabs-2.2.4 TAF Publishing Yeoh & Koronios, 2010). Again, there are very few studies that have looked at the post-adoption effects of BI Systems on organizational performance (Elbashir, Collier, & Davern, 2008;Hou, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other published work on critical success factors (Yeoh & Koronios (2010) and Olszak & Ziemba (2012)) focuses on CSFs for implementing BI systems; however Shanks & Bekmamedova (2012) have presented results from a project where they studied a large Australian financial services firm and found critical success factors that helped increase analytical maturity. In addition, when appropriate, we also use complementary theory as a means to introduce different perspectives and for being able to make the discussion concerning our case study as detailed and extensive as possible.…”
Section: Key Obstacles Data Managementmentioning
confidence: 99%